Chaotic nation - Entwine (yhtye); Hanttu, Aki, 1979-; Miettinen, Joni; Kähkönen, Jaani; Tauriainen, Mika, 1975-; Mikkola, Tom; Universal Music Oy ([Kustannuspaikka tuntematon] : Universal Music, 2015)
10 kappaletta.
End of silence ; Saint of sorrow ; Fortune falls ; Plastic world ; As we rise ; Lost but still alive ; Adrenalize ; The evil lives in the shadows ; Revolt for redemption ; Scream.
Entwine (yhtye): Aksu Hanttu (rummut), Joni Miettinen (sähköbasso), Mika Tauriainen (lauluääni), Jaani Kähkönen (kitara), Tom Mikkola (kitara).
Sanat: englanti.
Keywords: Entwine (yhtye) -- albumit; heavy metal; death metal